Attitudes towards risk‐reducing early salpingectomy with delayed oophorectomy for ovarian cancer prevention: a cohort study. (16th August 2020) - Gaba, F; Blyuss, O; Chandrasekaran, D; Osman, M; Goyal, S; Gan, C; Izatt, L; Tripathi, V; Esteban, I; McNicol, L; Ragupathy, K; Crawford, R; et al.
Abstract : Objective: To determine risk‐reducing early salpingectomy and delayed oophorectomy (RRESDO) acceptability and effect of surgical prevention on menopausal sequelae/satisfaction/regret in women at increased ovarian cancer (OC) risk. Design: Multicentre, cohort, questionnaire study (IRSCTN:12310993). Setting: United Kingdom (UK). Population: UK women without OC ≥18 years, at increased OC risk, with/without previous RRSO, ascertained through specialist familial cancer/genetic clinics and BRCA support groups. Methods: Participants completed a 39‐item questionnaire. Baseline characteristics were described using descriptive statistics. Logistic/linear regression models analysed the impact of variables on RRESDO acceptability and health outcomes. Main outcomes: RRESDO acceptability, menopausal sequelae, satisfaction/regret. Results: In all, 346 of 683 participants underwent risk‐reducing salpingo‐oophorectomy (RRSO). Of premenopausal women who had not undergone RRSO, 69.1% (181/262) found it acceptable to participate in a research study offering RRESDO. Premenopausal women concerned about sexual dysfunction were more likely to find RRESDO acceptable (odds ratio [OR] = 2.9, 95% CI 1.2–7.7, P  = 0.025). Women experiencing sexual dysfunction after premenopausal RRSO were more likely to find RRESDO acceptable in retrospect (OR = 5.3, 95% CI 1.2–27.5, P  < 0.031). In all, 88.8% (143/161) premenopausal and 95.2% (80/84) postmenopausal women who underwent RRSO, respectively, were satisfied with their decision, whereas 9.4% (15/160) premenopausal and 1.2% (1/81) postmenopausal women who underwent RRSO regretted their decision. HRT uptake in premenopausal individuals without breast cancer (BC) was 74.1% (80/108). HRT use did not significantly affect satisfaction/regret levels but did reduce symptoms of vaginal dryness (OR = 0.4, 95% CI 0.2–0.9, P  = 0.025). Conclusion: Data show high RRESDO acceptability, particularly in women concerned about sexual dysfunction. Although RRSO satisfaction remains high, regret rates are much higher for premenopausal women than for postmenopausal women. HRT use following premenopausal RRSO does not increase satisfaction but does reduce vaginal dryness. Tweetable abstract: RRESDO has high acceptability among premenopausal women at increased ovarian cancer risk, particularly those concerned about sexual dysfunction. Tweetable abstract: RRESDO has high acceptability among premenopausal women at increased ovarian cancer risk, particularly those concerned about sexual dysfunction.